COMPORTAMENTO DE CULTIVARES DE FEIJÃƒO (ð˜—ð˜ð˜ˆð˜šð˜Œð˜–ð˜“ð˜œð˜š ð˜ð˜œð˜“ð˜Žð˜ˆð˜™ð˜ð˜š L.) EM REGENTE FEIJÃ“. EXPERIMENTO II. - Nakagawa, JoÃ£o; Nakagawa, JÃºlio; Machado, JosÃ© Ricardo (REVISTA DE AGRICULTURA, 2020)
COMPORTAMENTO DE CULTIVARES DE FEIJÃƒO (ð˜—ð˜ð˜ˆð˜šð˜Œð˜–ð˜“ð˜œð˜š ð˜ð˜œð˜“ð˜Žð˜ˆð˜™ð˜ð˜š L.) EM REGENTE FEIJÃ“. EXPERIMENTO II.